Powering Predictions for United States Coast Guard Proposed Icebreaker Designs Represented by Models 5140, 5141, and 5142. - Day, William G., Jr (1968)
The report presents the results of powering propulsion tests. The tests include towing at three speeds including zero speed, and backing at full power at zero speed as well as free running power requirements for three models which were considered candidates for the hull design of a medium polar icebreaker for the U. S. Coast Guard. Revision of report dated Aug 67, AD-845 541L.